A Push-pull based Application Multicast Layer for P2P live video streaming - Bùi, Thị Lan Hương (ĐHCN, 2017)
With the rapid growth of multimedia applications and the Internet, streaming video over the Internet is becoming more and more attractive to users especially live video streaming. Many application-layer multicast pro-tocols have been proposed recently for...